Efektivitas Penerapan Tracer Terhadap Pengendalian Kejadian Missfile Rekam Medis Di UPTD Puskesmas Rendang - Ni Luh Ayu Winda Mahayani; Agus Donny Susanto; Dylla Hanggaeni Dyah Puspaningrum (Jurnal Yoga dan Kesehatan, 2023)
UPTD Puskesmas Rendang has not applicated a medical record tracer (exit instructions) so that there are still misplaced or no medical records found on the storage rack that caused missfile. Based on a preliminary study conducted in December 2021, it was found that the percentage of missfile events was 10.53% of 1,680 medical records. Puskesmas Rendang  requires a medical record tracer that could overcome the problem of medical record missfiles. The purpose of this study is to design a medical record tracer and measure the effectiveness of the application of the tracer. The research design used is One Group Pretest-Postest Design, which is to measure the number of missfile events before and after the application of the medical record tracer. The results of this study are using a questionnaire test with a Likert scale, the results obtained are 85% whose feasibility can be categorized as "Very Eligible". The results of hypothesis testing using the Wilcoxon Signed Ranks Test obtained a significance value of 0.000 so that 0.000 <0.05. Based on the results, it concluded that there is an effectiveness of the application of tracer to control the incidence of missfile medical records in the UPTD Puskesmas Rendang. It suggests that the development of an electronic-based medical record tracer is needed so that the service process can run effectively and efficiently. Furthermore, retention is also required.